2019
DOI: 10.1063/1.5109964
|View full text |Cite
|
Sign up to set email alerts
|

Non-adiabatic mass correction for excited states of molecular hydrogen: Improvement for the outer-well HH¯ 1Σg+ term values

Abstract: The mass-correction function is evaluated for selected excited states of the hydrogen molecule within a single-state non-adiabatic treatment. Its qualitative features are studied under the avoided crossing of the EF with the GK state and also for the outer well of the HH state. For the HH state, a negative mass correction is obtained for the vibrational motion near the outer minimum, which accounts for most of the deviation between experiment and earlier theoretical work. * Electronic address: matyus@chem.elte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…This feature was computed already in Ref. [21], and it was found that correction of the constant, nuclear (proton) mass by this non-adiabatic term the deviation of theory and experiment is reduced by an order of magnitude, i.e., from ca. 1 cm −1 to ca.…”
Section: Mass Correction For Coupled Electronic Manifoldsmentioning
confidence: 59%
See 3 more Smart Citations
“…This feature was computed already in Ref. [21], and it was found that correction of the constant, nuclear (proton) mass by this non-adiabatic term the deviation of theory and experiment is reduced by an order of magnitude, i.e., from ca. 1 cm −1 to ca.…”
Section: Mass Correction For Coupled Electronic Manifoldsmentioning
confidence: 59%
“…The single-state mass correction, Eq. ( 8), has been formulated several times [13][14][15][16] and was successfully used in spectroscopic applications [15,[17][18][19][20][21][22]. We are not aware of any computation with the multi-state expression, Eqs.…”
Section: Nuclear-motion Hamiltonian Over Coupled Electronic Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…For a quantitative description of the high-resolution spectroscopic measurements of atoms [1,2] and molecules [3,4], calculations of highly accurate energies are required corresponding to an at least parts-per-billion (ppb) relative precision [5][6][7]. To ensure a ppb-level of convergence for atomic and molecular energies, it is necessary to use explicitly correlated basis functions [6,[8][9][10]. Although fast convergence of the energy with respect to the basis set size is ensured, most explicitly correlated functions are highly specialised to the particular system.…”
Section: Introductionmentioning
confidence: 99%